Landscape Genomics in Tree Conservation Under a Changing Environment - Feng, Li; Du, Fang K. (Frontiers in Plant Science, 2022)
Understanding the genetic basis of how species response to changing environment is essential to the conservation of species. However, the molecular mechanisms of adaptation remain largely unknown for long-lived tree species which always have large population sizes, long generation time, and extensive gene flow. Recent advances of landscape genomics can reveal the signals of adaptive selection linking genetic variations and landscape characteristics and therefore have created novel insights into tree conservation strategies. In this review paper, we first summarize methods of landscape genomics used in tree conservation and elucidate the advantages and disadvantages of these methods. We then highlight the newly developed method “Risk of Non-Adaptedness”, which can predict the genetic offset or genomic vulnerability of species via allele frequency change under multiple scenarios of climate change. Finally, we provide prospects concerning how our introduced approaches of landscape genomics can assist policy making and improve existing conservation strategies for tree species under the ongoing global changes.